Deaf Children and Adolescents: Social Skills Discriminant Profile - Rafaela Fava de Quevedo; Ilana Andretta (Psicologia: Teoria e Pesquisa, 2021)
Abstract The objectives of the study were to compare social skills among deaf children and adolescents and to outline the discriminant profile in relation to skilled social behaviors. The research had a quantitative, cross-sectional and comparative design. Seventy-one deaf people aged 7 to 16 years old participated in the study, assessed by a sociodemographic questionnaire and by the Social Skills Test for Children and Adolescents in School Situation. Results revealed that deaf adolescents have more elaborate social skills when compared to deaf children. Children have a profile related to the Conversation and Social Resourcefulness and Assertiveness while adolescents were included in the Civility and Altruism profile. These results were discussed based on the development and specificities of deafness. Future research may assess these skills beyond the school settings.